Electropolymerized polyaniline: A promising hole selective contact in organic photoelectrochemical cells. (2nd November 2016) - Belarb, Eya; Blas-Ferrando, Vicente M.; Haro, Marta; Maghraoui-Meherzi, Hager; Gimenez, Sixto
Abstract: In the present study, we have prepared Polyaniline (PANI) thin films by electrochemical polymerization on ITO substrates in acidic medium at room temperature. We have followed a systematic modification of both the precursor concentration as well as the number of electropolymerization cycles in order to optimize the response of the films as hole selective contacts for organic photoelectrochemical cells. We report the structural, optical and electrochemical properties of the PANI films aiming at providing such optimized hole selective contacts. Our results clearly confirm that PANI acts as efficient hole selective layer in these devices, with photocurrents of more than 2 mA cm −2 at −0.5 V vs RHE, and 0.3 mA cm −2 at 0 V vs RHE for hydrogen generation and further modifications should be focused on enhancing the device stability for technological application. Highlights: PANI films were processed with a systematic modification of the processing conditions. The structural, optical and photoelectrochemical properties of the films are reported. Optimized PANI films constitute promising hole selective contacts for OPECs. Photocurrents >2 mA cm −2 at −0.5 V vs RHE for hydrogen generation are reported. Further stabilization strategies should be employed.